Brainstem-Evoked Transcription of Defensive Genes After Spinal Cord Injury - Jermakowicz, Walter J.; Carballosa-Gautam, Melissa M.; Vitores, Alberto A.; Hentall, Ian D. (Frontiers in Cellular Neuroscience, 2019)
The spinal cord after injury shows altered transcription in numerous genes. We tested in a pilot study whether the nucleus raphé magnus, a descending serotonergic brainstem region whose stimulation improves recovery after incomplete spinal cord injury, can influence these transcriptional changes. Rats received 2 hours of low-frequency electrical stimulation in the raphé magnus three days after an impact contusion at segment T8. Comparison groups lacked injuries or activated stimulators or both. Immediately following stimulation, spinal cords were extracted, their RNA transcriptome sequenced, and differential gene expression quantified. Confirming many previous studies, injury primarily increased inflammatory and immune transcripts and decreased those related to lipid and cholesterol synthesis and neuronal signaling. Stimulation plus injury, contrasted with injury alone, caused significant changes in 43 transcripts (39 increases, 4 decreases), all protein-coding. Injury itself decreased only four of these 43 transcripts, all reversed by stimulation, and increased none of them. The non-specific 5-HT7 receptor antagonist pimozide reversed 25 of the 43 changes. Stimulation in intact rats principally caused decreases in transcripts related to oxidative phosphorylation, none of which were altered by stimulation in injury. Gene ontology (biological process) annotations comparing stimulation with either no stimulation or pimozide treatment in injured rats highlighted defense responses to lipopolysaccharides and microorganisms, and also erythrocyte development and oxygen transport (possibly yielding cellular oxidant detoxification). Connectivity maps of human orthologous genes generated in the CLUE database of perturbagen-response transcriptional signatures showed that drug classes whose effects in injured rats most closely resembled stimulation without pimozide include peroxisome proliferator-activated receptor agonists and angiotensin receptor blockers, which are reportedly beneficial in spinal cord injury. Thus the injured spinal cord responds initially to raphé magnus stimulation mainly by turning on genes that are in various ways protective, some probably located in recently arrived myeloid cells.